A framework for distributed mobile applications - Zawawi Ismail @ Abdul Wahab (Fakulti Sains dan Teknologi, 2012)
The world of computing is moving towards a computing environment where the computing services are virtually and ubiquitously embedded into the world of human. This is known as pervasive computing. It is a computing environment that aims to provide computing services available anytime, anywhere and on demand.